Comparative Effectiveness and Safety of Allografts and Autografts in Posterior Cruciate Ligament Reconstruction Surgery: A Systematic Review - Cecilia de Villiers, M.Sc., B.Sc; Gregor Goetz, M.S.Sc., M.P.H; Patrick Sadoghi, M.D., Ph.D., M.B.A; Sabine Geiger-Gritsch, D.M.Sc., M.H.Sc., M.Pharm (Elsevier, 2020)
Purpose: To evaluate the evidence of the effectiveness and safety of allografts compared to autografts in posterior cruciate ligament reconstruction. Methods: Four electronic databases were systematically searched for eligible randomized controlled studies. Crucial effectiveness outcomes included patient-reported function, activity level and symptoms, clinical knee stability, health-related quality of life, and patient satisfaction. Safety was evaluated through graft failures, revisions, reruptures and complications. The internal validity of the studies was assessed by the Cochrane risk of bias tool, and the strength of the evidence was judged according to the Grading of Recommendations, Assessment, Development and Evaluation (GRADE). Results: Two randomized controlled studies were included: 50 patients were analyzed in the allograft group and 58 in the autograft group. No statistically significant postoperative differences were reported between the groups for patient-reported function, activity levels or symptoms. One study reported a statistically significant difference in instrumented postoperative anteroposterior knee laxity favoring stability in autografts. This difference is, however, not relevant in the clinical setting. Insufficient evidence was found to judge safety outcomes and because complications were poorly measured, and none of the studies reported on graft failure, revision or rerupture rates. The studies were judged with unclear to high risk of bias. The strength of the evidence for effectiveness and safety was judged to be low to very low, according to GRADE. Conclusions: Allografts may be comparable to autografts for crucial effectiveness outcomes, but insufficient evidence was found to judge crucial safety outcomes due to poor reporting of safety measures and outcomes. Results should be interpreted with caution because there is lack of good-quality evidence to support the superiority of allografts over autografts due to the high risk of bias in the primary studies and overall very low strength of the body of evidence according to GRADE. Level of Evidence: Systematic review of Level II studies.